2020
DOI: 10.1038/s41433-020-0876-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of treating meibomian gland dysfunction with azithromycin

Abstract: To systematically review studies of managing meibomian gland dysfunction (MGD) with azithromycin and pool clinical outcomes to show its effectiveness. Eligible studies were retrieved from five main electronic databases. Symptom score was the primary outcome, while clinical signs and objective measurements were secondary outcomes. Pooled rates for adverse events were also calculated. Improvements in each outcome after administering either oral azithromycin (OA) or topical azithromycin (TA) were pooled and measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
(51 reference statements)
1
14
0
1
Order By: Relevance
“…Both azithromycin and tetracycline derivatives have been shown to improve MGD symptoms and meibomian gland function. A recent meta-analysis of 15 trials examining oral and topical azithromycin treatment by Tao et al [45] demonstrated significant improvements in symptom scores, meibomian gland physiology and tear film characteristics. Similar findings have been found in clinical trials using oral tetracyclines [46,47].…”
Section: Current State Of Meibomian Gland Dysfunction Treatmentmentioning
confidence: 99%
“…Both azithromycin and tetracycline derivatives have been shown to improve MGD symptoms and meibomian gland function. A recent meta-analysis of 15 trials examining oral and topical azithromycin treatment by Tao et al [45] demonstrated significant improvements in symptom scores, meibomian gland physiology and tear film characteristics. Similar findings have been found in clinical trials using oral tetracyclines [46,47].…”
Section: Current State Of Meibomian Gland Dysfunction Treatmentmentioning
confidence: 99%
“…Так, например, антибиотики тетрациклинового ряда (доксициклин) ингибируют продукцию бактериальных липаз, улучшая тем самым липидный профиль мейбомиевых масел. Местное применение азитромицина оказывает и антибактериальное, и противовоспалительное действие [39,40].…”
Section: обзоры противовоспалительная терапия синдрома «сухого глаза»unclassified
“…However, the World Health Organization advises limiting the prescription of antibiotics to slow the development of antibiotic resistance [12]. Recent reviews have found that oral and topical antibiotics are effective in treating MGD and MGD-related DED, especially in the short-term [13][14][15][16][17]. However, despite their widespread use, level I clinical evidence (randomized, placebo-controlled trials) supporting the use of oral antibiotics in the treatment of MGD and MGD-related DED is limited [13,14,16].…”
Section: Introductionmentioning
confidence: 99%